Identification of key oxidative intermediates and the function of chromium dopants in PKU-8: catalytic dehydrogenation of sec-alcohols with tert-butylhydroperoxide. Issue 4 (24th December 2020) - Wang, Weilu; He, Yang; He, Junkai; Dang, Yanliu; Kankanmkapuge, Tharindu; Gao, Wenliang; Cong, Rihong; Suib, Steven L.; Yang, Tao
Abstract : t -BuOO* activated by Cr-PKU-8 from TBHP is the key intermediate to the highly selective dehydrogenation of sec -alcohols. Abstract : Catalytic oxidation reaction using green oxidants plays an important role in modern chemical engineering; however, the in situ generated active species and the related catalytic mechanism need to be understood in depth. For this purpose, Cr-substituted aluminoborate Cr-PKU-8 catalysts were synthesized and applied as recyclable heterogeneous catalysts for the oxidation of aliphatic and aromatic alcohols using tert -butylhydroperoxide (TBHP). Both high efficiency and selectivity (>99%) were achieved during the dehydrogenation of various sec -alcohols into acetone in H2 O solvent medium. From the analyses using isotopic tracer, molecular probe and cyclic voltammetry strategies, the chromium ions were observed to undergo a Cr 3+ –Cr 2+ –Cr 3+ redox cycle. DFT calculations suggest that t -BuOO* is more energetically favourable for hydrogen abstraction from sec -alcohol than t -BuO*, and probably acts as the key active species. Accordingly, the reaction scheme was proposed to interpret the catalytic process based on the observed results.